Pengaruh Kompensasi dan Pengembangan Karir terhadap Kinerja Karyawan di PT Inasentra Unisatya - Yohana Dian Vanessa; Asep Dony Suhendra (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2024)
Every company has a role for employees in carrying out all activities within a company. Employees are an important part that has a huge influence on the success of a company. Therefore, companies need to pay more attention to employee performance so that they are more active, especially in terms of compensation and career development. This research aims to determine the effect of compensation and career development on employee performance at PT. Inasentra Unisatya. The research method used is a quantitative approach. Data collection methods in this research are interviews, questionnaires and literature study. The population in this study were permanent employees of PT. Inasentra Unisatya in the field of personnel has 53 employees.. The sampling technique used was quota sampling with a sample size of 30 respondents. The data analysis techniques used are data quality testing, classical assumption testing, hypothesis testing, and coefficient of determination testing which are processed using the SPSS version 25.0 application.. The results of this research show that compensation partially has a positive and significant effect on employee performance. Career development partially has a positive and significant effect on employee performance. Simultaneously compensation and career development have a positive and significant effect on employee performance.